Strategi Pembelajaran Pendidikan Agama Islam Berbasis Fikih di STIKes Widya Dharma Husada Tangerang - Ma'muroh Ma'muroh; Rohanah Rohanah; Yulia Yulia; Liza Puspa Dewi (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2025)
Study purpose. This study aims to examine and analyze the instructional strategies of Islamic Religious Education (PAI) based on fiqh implemented at STIKes Widya Dharma Husada (WDH) Tangerang within the context of nursing education. This research is motivated by the importance of integrating Islamic values, particularly Islamic jurisprudence (fiqh), into the development of ethical and spiritual competencies among nursing students in accordance with the 2021 AIPNI Curriculum. Material and method. A qualitative approach with a case study design was employed, involving PAI lecturers, students, and curriculum developers as research subjects. Data were collected through in-depth interviews, participatory observation, and document analysis, and were analyzed thematically. The findings reveal that the applied teaching strategies include Problem-Based Learning (PBL), thematic discussions, and contextual simulations. Results. These strategies have been proven effective in enhancing students’ understanding of fiqh and fostering ethical and religious awareness in nursing practice. The lesson plans and syllabi explicitly demonstrate the integration of fiqh into learning outcomes. Students expressed positive responses to the contextual and interactive approach, although several challenges were noted, including limited instructional time and the availability of supporting materials. This study concludes that the application of fiqh-based PAI teaching strategies at STIKes WDH effectively contributes to shaping Islamic character within the nursing profession. Cunclosions. The results offer both theoretical and practical contributions to the development of religious education models in health-related higher education institutions.